2021
DOI: 10.1049/ell2.12296
|View full text |Cite
|
Sign up to set email alerts
|

Research on obstacle climbing gait of snake‐like robot on high‐voltage cables cables

Abstract: Aiming at the gait control problem of a snake-like inspection robot performing variable-diameter spiral motion on high-voltage cables, a gait generation method is proposed here, the snake-like robot can adapt to the change in diameter when it is winding around the obstacles of highvoltage cables. The piecewise helix is fitted with the Bezier curve of degree 3, which solves the problem of discontinuous speed and abrupt change of joint angle when the snake-like robot moves with variable diameter, and avoids peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[50][51][52] As shown in Figure 11, the application prospects of 3D printed dielectric elastomers or dielectric elastomer actuators are broad. The production printed by 3D printers can be used in the deep sea, planetary surfaces, 57 narrow confined spaces, high-voltage cables, 58 and other unstructured environments. Soft robots with modular structures have shown great advantages in industry, medical field, 59 post-disaster search and rescue fields.…”
Section: D Printing Of Dielectric Elastomer Actuatorsmentioning
confidence: 99%
“…[50][51][52] As shown in Figure 11, the application prospects of 3D printed dielectric elastomers or dielectric elastomer actuators are broad. The production printed by 3D printers can be used in the deep sea, planetary surfaces, 57 narrow confined spaces, high-voltage cables, 58 and other unstructured environments. Soft robots with modular structures have shown great advantages in industry, medical field, 59 post-disaster search and rescue fields.…”
Section: D Printing Of Dielectric Elastomer Actuatorsmentioning
confidence: 99%
“…The snake-inspired robots as a continuum robot (Wei et al , 2020) have reconfigurable modular structural units and unique merits in using its whole body’s flexible deformation for locomotion and grasping. Therefore, it can also be used in the deep sea (Ludvigsen and Sørensen, 2016), planetary surface (Hou et al , 2020; Liu et al , 2016), narrow confined spaces (Brunete et al , 2012), high-voltage cables (Wei et al , 2014; Yang et al , 2021) and other unstructured environments. Meanwhile, snake-inspired robots with modular structures and multiple gaits (Wang et al , 2017) have shown great advantages in industrial field, military field, medical field and post-disaster search and rescue fields (Jin et al , 2019; Zhang and Lu, 2020).…”
Section: Application Prospectmentioning
confidence: 99%